Розробка методики калібрування неавтоматичних зважувальних приладів - Калган, В. В. (ХНУРЕ, 2025)
This study focuses on developing a calibration methodology for nonautomatic weighing instruments to ensure accuracy and compliance with metrological standards. The research outlines key calibration stages, including preparation, selection of test weights, measurement execution, data analysis, and certification. It highlights challenges such as environmental influences, weight positioning, and measurement uncertainties. Proper calibration enhances the reliability of weighing instruments in various industries, including manufacturing, trade, laboratory research, and quality control, ultimately ensuring precise and standardized mass measurements.
Keywords: калібрування зважувальних приладів; зважувальний прилад